Laura J. Gorfkle, Discovering the comic in "Don Quijote". The University of North Carolina, Chapel Hill, 1993; 227 pp. (North Carolina Studies in the Romance Languages and Literature, 243). - Gabriel Enrique Linares González (Nueva Revista de Filología Hispánica, 1997)
Se reseñó el libro: Discovering the comic in "Don Quijote".